STANDARDIZATION OF CLINICAL PHARMACIST FUNCTIONAL RESPONSIBILITIES IN HOSPITAL SETTING IN UKRAINE AND ABROAD - Andriy Zimenkovsky; Х.І. Макух; Myroslava Sekh; Marta Zayats (Acta Medica Leopoliensia)
Aim. Collection, analysis, and standardization of practical functions of a clinical pharmacist in national and foreign inpatient health care facilities, as well as identification of barriers during the integration of clinical pharmacy services in Ukraine.